Timely diagnosis of pulmonary artery tumor embolism by ultrasound‐guided transbronchial needle aspiration. Issue 2 (March 2014) - Lee, Seung Jun; Lee, Jinwoo; Yu, Su Jong; Lee, Hyun Ju; Kim, Kyung Ju; Lee, Kyoung‐Bun; Park, Young Sik
Abstract Pulmonary artery tumor embolism (PATE) is a rare disease without an established diagnostic method. In an autopsy series, however, the incidence of PATE was relatively high, between 3% and 26% in patients with a solid tumor. Here we report a case of a patient with a massive PATE from hepatocellular carcinoma diagnosed safely and promptly by endobronchial ultrasound‐guided transbronchial needle aspiration.